Hormone replacement therapy in morphine-induced hypogonadic male chronic pain patients - Aloisi, Anna Maria (BioMed Central, 2011)
BACKGROUND: In male patients suffering from chronic pain, opioid administration induces severe hypogonadism, leading to impaired physical and psychological conditions such as fatigue, anaemia and depression. Hormone replacement therapy is rarely considered for these hypogonadic patients, notwithstanding the various pharmacological solutions available. METHODS: To treat hypogonadism and to evaluate the consequent endocrine, physical and psychological changes in male chronic pain patients treated with morphine (epidural route), we tested the administration of testosterone via a gel formulation for one year. Hormonal (total testosterone, estradiol, free testosterone, DHT, cortisol), pain (VAS and other pain questionnaires), andrological (Ageing Males' Symptoms Scale - AMS) and psychological (POMS, CES-D and SF-36) parameters were evaluated at baseline (T0) and after 3, 6 and 12 months (T3, T6, T12 respectively). RESULTS: The daily administration of testosterone increased total and free testosterone and DHT at T3, and the levels remained high until T12. Pain rating indexes (QUID) progressively improved from T3 to T12 while the other pain parameters (VAS, Area%) remained unchanged. The AMS sexual dimension and SF-36 Mental Index displayed a significant improvement over time. CONCLUSIONS: In conclusion, our results suggest that a constant, long-term supply of testosterone can induce a general improvement of the male chronic pain patient's quality of life, an important clinical aspect of pain management.